PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA MENGAJAR GURU DI SEKOLAH DASAR NEGERI SE-KECAMATAN SUKASARI KOTA BANDUNG - Nuraisah, - (2021)
This research entitled "the Influence of Transformational Leadership of the principal on the Performance of Teachers in Sekolah Dasar Negeri Se-Kecamatan Sukasari Kota Bandung". This study aims to obtain an overview of the Influence of Transformational Leadership of the principal on the Performance of Teachers in Sekolah Dasar Negeri Se-Kecamatan Sukasari Kota Bandung. This research uses descriptive method with quantitative approach. Data collection techniques using questionnaires that were distributed to 15 Sekolah Dasar Negeri Se-Kecamatan Sukasari, with the respondent the Teacher. Based on the calculation of the Level of Achievement of the Respondents (TCR) the Teachers showed that the transformational leadership of principals and the performance of the teachers are in very good category with a value of 90,1 and 92,3. Furthermore, the resultsof the normality test data show that the variable X and variable Y is normally distributed, so the analysis of the data using parametric statistics. Based on the results of the hypothesistest, it is known that there is influence of the strong and significant correlation between transformational leadership of the principal on the performance of teachers in Sekolah Dasar Negeri Se-Kecamatan Sukasari, with the value of the correlation coefficient of 0,668and the value of the significance test of 7,451 which proved significant because t_hitung (7,451) > t_tabel (1,995); while the results of the analysis of the coefficient of determination of 44,6%, this illustrates that the influence of Transformational Leadershipof the principal on the Performance of the information collected in the Teacher of 44,6% and of 55,4% is influenced by other factors. Based on the results above, shows that there isinfluence of Transformational Leadership of the principal on the Performance of Teachers in Sekolah Dasar Negeri Se-Kecamatan Sukasari Kota Bandung.